The Contribution Of The Legal Political-Administrative Developments Of The Tanzimat Period To The Democracy - Uluç, A.vahap; Kaan, Oğuz (Fırat University, 2022)
Turkey's democracy adventure is almost as old as the history of modernization. Because the institutions and rules needed by democracy emerged with modernism. Therefore, it is possible to take the first examples of the democracy process back to the Tulip Era. However, the period in which the institutions and rules that will contribute to the development of democracy are embodied in the Tanzimat Period, in which the modernization move intensified. Democracy is defined as a regime that is based on popular sovereignty, based on the rule of law, considers everyone as a citizen without making any religious or ethnic discrimination among citizens, is organized according to the principle of division of powers, and powers are shared between central and local actors. In this sense, the reforms made in the Tanzimat Period took the lead in shaping the institutions and legal regulations needed by democracy, which would find its meaning in the Republican Period. The principals in the Tanzimat Edict and Islahat Edict and legal arrangements, assemblies formed in order to put the principles into effect have made very serious contributions to democracy. Ensuring the safety of people's life and property, the limitation of the Sultan's powers, the reflection of the will of the people on the administration through the established assemblies, the legal regulations imported from European countries regarding social and economic life, the efforts to transform local governments into Western-style institutions reveal the contribution of the Tanzimat Reforms to democracy.

Türkiye’nin demokrasi serüveni neredeyse modernleşme tarihi kadar eskidir. Çünkü demokrasinin ihtiyaç duyduğu kurum ve kurallar modernizm ile birlikte ortaya çıkmıştır. Dolayısıyla demokrasi sürecine ilişkin ilk örnekleri Lale Devri’ne kadar götürmek mümkündür. Ancak demokrasinin gelişimine katkıda bulunacak kurum ve kuralların ete kemiğe büründüğü dönem modernleşme hamlesinin yoğunluk kazandığı Tanzimat Dönemi’dir. Demokrasi, halk egemenliğine dayanan, hukukun üstünlüğünü esas alan, vatandaşlar arasında din, etnik ayırımı yapmadan herkesi yurttaş olarak gören, kuvvetler ayrılığı ilkesine göre teşkilatlanmış, yetkilerin merkez ile yerel aktörler arasında paylaştırıldığı bir rejim olarak ifade edilir. Tanzimat Dönemi’nde yapılan reformlar bu anlamda Cumhuriyet Döneminde anlamını bulacak demokrasinin ihtiyaç duyduğu kurumların ve yasal düzenlemelerin biçimlenmesinde ön ayak olmuştur. Tanzimat Fermanı ve Islahat Fermanı'nda geçen ilkeler ile bu iki belgede geçen ilkeleri yürürlüğe koymak bağlamında yapılan hukuki düzenlemeler ve oluşturulan meclisler demokrasiye çok ciddi katkılar sunmuştur. Kişilerin can ve mal güvenliğinin sağlanması, Padişahın yetkilerinin sınırlandırılması, kurulan meclisler aracılığı ile halk iradesinin yönetime yansıması, sosyal ve ekonomik hayata ilişkin Avrupa ülkelerinden ithal edilen yasal düzenlemeler, yerel yönetimlerin Batı tarzı kurumlara dönüştürülme çabaları Tanzimat Dönemi reformlarının demokrasiye katkısını ortaya koymaktadır.
HUKUKİ VE SİYASİ-İDARİ AÇIDAN TANZİMAT DÖNEMİ GELİŞMELERİNİN DEMOKRASİYE KATKISI